Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPS Kelas IV SD Inpres Macanda Kecamatan Somba Opu Kabupaten Gowa - Wahyuni, Sri; Hasan Basri; Nursalam; Syarifah Aeni Rahman (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to determine the effect of the Problem Based Learning (PBL) model on students' critical thinking abilities in the Class IV Social Sciences subject at SD Inpres Macanda, Somba Opu District, Gowa Regency. This type of research is experimental research in the form of One Group Pre Test Post Test Design. The data collection techniques used are observation, critical thinking ability tests. The data analysis technique uses descriptive analysis and inferential analysis. The results of the research show that the critical thinking abilities of fourth grade students at SD Inpres Macanda before implementing the Problem Based Learning (PBL) model were categorized as still low. This can be seen from the average student pre-test score of 55.34. After implementing the Problem Based Learning (PBL) model, the critical thinking ability of fourth grade students at SD Inpres Macanda, Somba Opu District, Gowa Regency was categorized as very high. The average post-test score was 83.10. The average value of the percentage results of learning implementation by applying the Problem Based Learning (PBL) model is 89.65.